An amino acid transporter‐like protein (OsATL15) facilitates the systematic distribution of thiamethoxam in rice for controlling the brown planthopper. Issue 10 (5th July 2022) - Xiao, Yuyan; Zhang, Hanlin; Li, Zhiwei; Huang, Tinghong; Akihiro, Takashi; Xu, Jian; Xu, Hanhong; Lin, Fei
Summary: Characterization and genetic engineering of plant transporters involved in the pesticide uptake and translocation facilitate pesticide relocation to the tissue where the pests feed, thus improving the bioavailability of the agrichemicals. We aimed to identify thiamethoxam (THX) transporters in rice and modify their expression for better brown planthopper (BPH) control with less pesticide application. A yeast library expressing 1385 rice transporters was screened, leading to the identification of an amino acid transporter‐like (ATL) gene, namely OsATL15, which facilitates THX uptake in both yeast cells and rice seedlings. In contrast to a decrease in THX content in osatl15 knockout mutants, ectopic expression of OsATL15 under the control of the CaMV 35S promoter or a vascular‐bundle‐specific promoter gdcsPpro significantly increased THX accumulation in rice plants, thus further enhancing the THX efficacy against BPH. OsATL15 was localized in rice cell membrane and abundant in the root transverse sections, vascular bundles of leaf blade, and stem longitudinal sections, but not in hull and brown rice at filling stages. Our study shows that OsATL15 plays an essential role in THX uptake and its systemic distribution in rice. OsATL15 could be valuable in achieving precise pest control by biotechnology approaches. Abstract : OsATL15 overexpression enhanced THX uptake and consequently, conferred more effective control of brown planthopper than that observed in wild‐type plants, whereas knocking out OsATL15 led to decreased accumulation of THX and increased damage by brown planthopper.